Uso de diagramas de Voronoi na determinação do zoneamento de risco e medidas de confiabilidades associadas à presença de poluentes atmosféricos - Bezerra, Alex Sandro da Silva (2011)
Atmospheric pollutants has become a major world concern for environmental and public health. Several studies have already addressed in this context about theme in order to verify the association between increased incidences of diseases with increased air pollution, mainly in cities where vehicle traffic has increased significantly. The pollution control is usually done by monitoring air quality through the sensor network. This monitoring network, besides being used as a tool for measuring public health safety, allow analyze the benefits gained by efforts to control the levels of air pollution and justify possible actions in case of breach of the thresholds established by legislation. The high costs involved and the difficulty inherent in the logistics of deployment and maintenance of the collection points can lead to an inappropriate placement or unrepresentative, if not carefully studied. Therefore, a good choice of site of insertion point is essential to provide greater efficiency in these costs. In this sense, the use of the weighted diagram Vononoi was used as a tool to determine the coverage area of each pollutant atmospheric sensor. After being realized the simulations, the coverage area of each sensor related with their own weight, were presented in a satisfactory way